Agricultural commodity futures - Ashok Gulati; Tirtha Chatterjee; Siraj Hussain (Indian Council for Research on International Economic Relations (ICRIER), 2017)
Agricultural futures markets can provide useful information to farmers for taking more informed planting decisions for their crops, which are forward looking, and thus reduce their market risk. But in India, agri-futures have gone through a roller-coaster ride since their mega opening in 2003, which does not bode well for farmers. As per our review and analysis, one of the principal reasons behind its lack-lustre performance has been unpredictable and perhaps excessive regulatory interventions in some commodities that appear to be sensitive in common man's consumption basket. These interventions often generate negative market sentiments and have detrimental impact on trade. We use Principal Component Analysis to identify criteria for assessing potential success of a commodity in agri-futures in India. We find that commodities that are relatively less sensitive from the perspective of food security of common man have higher prospect of success in agri-futures than say staple food commodities. Thus, the lessons learnt are that futures market can be deepened in India by (1) focusing first on "non-sensitive" commodities which are less susceptible to Government intervention. The portfolio can later be diversified, once agri-futures attain a sufficiently large scale. (2) Given the fluctuations in domestic production, consumption and global trade, these prospects need to be reviewed at regular intervals, (3) Developing delivery based contracts will increase the comfort of the regulator and policy maker, thus helping to deepen agri-futures in India, (4) Government of India can encourage its State Trading Enterprises to trade on agri-futures platform so that they have better information and comfort about the dynamics of these markets. (5) make it more attractive by allowing global players and Indian importers currently hedging in exchanges in foreign countries, especially for edible oils such as palm and soya oils and (6) developing agri-futures is as much the responsibility of the regulator as that of Commodity Exchanges, and both need to work in harmony for the benefit of various stakeholders.
Keywords: G10; G13; Q02; Q18; 330; Agriculture; Futures market; Potential; Criteria; Principal Component Analysis